Disharmonized the Regulation of Biological Resources and its Ecosystem in Indonesia - Simaremare, Sumurung P.; Noho, Muhammad Dzikirullah H. (International Journal of Criminology and Sociology, 2021)
The goal of state control over natural resources is an anticipatory step to avoid the widest possible use by individuals or legal entities as a means of oppression and exploitation of others. However, in reality, many regulations overlap and are not in harmony with one another. The author of this study uses normative juridical research. The definition of normative juridical is a type of research that emphasizes more on library research, where the materials used will be obtained from laws, literature, mass media, which are related to writing materials. This study found that the arrangement of living natural resources in Indonesia that is less harmonious is: a. Law Number 21 of 2004 concerning Ratification of the Cartagena Protocol On Biosafety To The Convention On Biological Diversity and b. Constitutional Court Decision No.35/PUU-X/2012. Keywords: Disharmonized, Regulation, Biological Natural Resources, Ecosystem, Indonesia.